STINGLESS BEE-DERIVED NATURAL COMPOUNDS AS ANTI-INFECTIVE AGENTS: COMPARATIVE GC-MS PROFILING OF Itama sp. AND Tetragonula laeviceps - Sintya, Erly (Meditory : The Journal of Medical Laboratory, 2025)
Background: Stingless bee honey is recognized for its therapeutic value, which is attributed to a diverse array of bioactive compounds.Objective:  This study aimed to compare the chemical profiles of honey from Tetragonula laeviceps and Itama sp. using gas chromatography-mass spectrometry (GC-MS), focusing on antimicrobial constituents. Methods: Honey samples were collected from Bali, Indonesia, and analyzed using GC-MS. Compounds were identified through spectral matching with established libraries, and primary constituents were compared based on relative abundance.Results:  T. laeviceps honey showed a high concentration of the rare sugar allose (7.6%), azulene (1.02%), and octadecanoic acid (2.07%), whereas Itama honey exhibited elevated levels of levoglucosan (5.35%), aromatic esters, and 3-methyl-2-furylacetone (2.58%). Notably, 5-hydroxymethylfurfural (HMF), known for its antimicrobial properties, was present in both samples at comparable levels (1–2%).Conclusions: The metabolite variations between the two species reflect differences in foraging and resin collection behavior, influencing honey bioactivity. The unique profiles suggest that both types of honey possess valuable antimicrobial potential and could serve as sources for developing novel anti-infective agents.